A model assisted ionospheric electron density reconstruction method based on vertical TEC data ingestion - Nava, Bruno (2005)
A technique to reconstruct the electron density of the ionosphere starting from total electron content values has been developed using the NeQuick ionospheric electron density model driven by its effective ionization parameter Az. The technique is based on the computation of Az values for a suitable worldwide grid of points. A simple way to obtain relevant Az grids is to use global vertical Total Electron Content (TEC) maps to define for each grid point as Az value, the one that minimizes the difference between the experimental and the modeled vertical TEC. Having a global grid of Az values it is possible to compute the electron density at any point in the ionosphere using NeQuick. As a consequence, slant TEC values for specific ground station to satellite links or ionosphere peak parameter values at any location can be calculated. The results of the comparisons between experimental and reconstructed slant TEC as well as experimental and reconstructed peak parameters values indicate that the proposed reconstruction method can be used to reproduce the observed ionosphere in a realistic way.